Quotas and Voice : Further Thoughts on Approaches to Reform. (Policy Papers; Policy Paper ;, 2006)
There is now widespread recognition that addressing quota and voice imbalances across the membership is essential for preserving the effectiveness of the Fund and its credibility as a cooperative institution. As noted in the Managing Director's Report on Implementing the Medium-Term Strategy,2 members' quotas have become increasingly out of line with countries' economic weight in the global economy. In addition, the declining role of basic votes since the Fund was established has weakened the voice of smaller developing countries.